2017
DOI: 10.1124/jpet.117.242321
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase 1 Is Required for Ethanol-Induced Locomotor Sensitization and Associated Increases in NMDA Receptor Phosphorylation and Function in the Dorsal Medial Striatum

Abstract: Neuroadaptive responses to chronic ethanol, such as behavioral sensitization, are associated with N-methyl-D-aspartate receptor (NMDAR) recruitment. Ethanol enhances GluN2B-containing NMDAR function and phosphorylation (Tyr-1472) of the GluN2B-NMDAR subunit in the dorsal medial striatum (DMS) through a protein kinase A (PKA)–dependent pathway. Ethanol-induced phosphorylation of PKA substrates is partially mediated by calcium-stimulated adenylyl cyclase 1 (AC1), which is enriched in the dorsal striatum. As such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Consistent with this nding, we found that hNB001, which can be used for the treatment of chronic pain in human, also did not affect acute nociceptive responses to mechanical stimuli and noxious thermal stimuli in naive mice. Previous studies showed that AC1 KO or NB001-treated mice exhibited normal motor functions and anxiety-like behavior (34,35). In the present study, hNB001 did not affect motor functions and anxiety-like behavior in naive adult mice (Table 1).…”
Section: Anxiety-like Behaviorsupporting
confidence: 56%
“…Consistent with this nding, we found that hNB001, which can be used for the treatment of chronic pain in human, also did not affect acute nociceptive responses to mechanical stimuli and noxious thermal stimuli in naive mice. Previous studies showed that AC1 KO or NB001-treated mice exhibited normal motor functions and anxiety-like behavior (34,35). In the present study, hNB001 did not affect motor functions and anxiety-like behavior in naive adult mice (Table 1).…”
Section: Anxiety-like Behaviorsupporting
confidence: 56%
“…Our findings that activation of G i/o signaling in the dorsal striatum reduces alcohol intake would suggest a role for adenylyl cyclase and cAMP in this behavior. Recently, reductions in cAMP levels in the dorsal striatum by adenylyl cyclase type 1 (AC1) inhibition and AC1-KO have been associated with decreased ethanol-induced locomotor sensitization ( 65 ). Furthermore, blockade of dorsal striatal G s -coupled dopamine D 1 receptors (but not blockade of G i/o -coupled dopamine D 2 ) attenuates alcohol consumption ( 8 ), suggesting indeed that inhibition of cAMP production in the dorsal striatum may contribute to reduced alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol affects receptor trafficking through changes e.g. in NMDA receptor phosphorylation and also neurosteroid synthesis is influenced by alcohol [614].…”
Section: Introductionmentioning
confidence: 99%